2016
DOI: 10.1097/mca.0000000000000388
|View full text |Cite
|
Sign up to set email alerts
|

Importance and usage of the CHA2DS2-VASc score in predicting acute stent thrombosis

Abstract: A CHA2DS2-VASc score of greater than 2 was found to be an independent predictor for incidence of ST. The role of the CHA2DS2-VASc score in predicting ST has not been investigated earlier in an AF-free population and our study is the first to explore this aspect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…Supporting the previous studies, this result suggests that CHADS2 VASc score may be indirectly associated with the development of noreflow [25]. Ünal et al demonstrated a relationship between acute stent thrombosis and CHA2DS2-VASc score in patients without atrial fibrillation [15]. In our study, CHA2DS2-VASc score was demonstrated to be an independent predictor of high thrombus burden.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Supporting the previous studies, this result suggests that CHADS2 VASc score may be indirectly associated with the development of noreflow [25]. Ünal et al demonstrated a relationship between acute stent thrombosis and CHA2DS2-VASc score in patients without atrial fibrillation [15]. In our study, CHA2DS2-VASc score was demonstrated to be an independent predictor of high thrombus burden.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the association between CHA2DS2-VASc score and acute stent thrombosis, noreflow, and thromboembolism and thrombosis in atrial fibrillation, which has been demonstrated in the previous studies may be helpful to explain the reason of its association with high thrombus burden in STEMI patients [8,15,25]. Again for the same reasons, we think it is not surprising to observe that CHADS VASc is a predictor of the development of high thrombus burden.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Similarly, in our cohort, elevated CHA 2 DS 2 VASc scores were associated with an increased incidence of in-hospital mortality. In a recent study on the association between CHA 2 DS 2 VASc scores and acute stent thrombosis in patients with stable coronary artery disease and acute coronary syndrome, a score of 3 or more had an independent predictive value for acute stent thrombosis [8]. We found similar results in our study with a larger cohort of only STEMI patients.…”
Section: Discussionsupporting
confidence: 81%
“…A previous study reported that the CHA 2 DS 2 VASc score was an independent predictor of in-hospital and long-term mortality in patients with acute coronary syndrome [7]. In addition, a recent study found an association between the CHA 2 DS 2 VASc score and acute stent thrombosis in patients with stable coronary artery disease [8]. In light of these data, the aim of the present study was to examine the potential utility of admission CHA 2 DS 2 VASc scores in predicting acute stent thrombosis in STEMI patients who have undergone a pPCI.…”
Section: Introductionmentioning
confidence: 99%